Answer:
x = 0
, y = 4
Step-by-step explanation:
Solve the following system:
{y = 4 - 3 x | (equation 1)
x + 2 y = 8 | (equation 2)
Express the system in standard form:
{3 x + y = 4 | (equation 1)
x + 2 y = 8 | (equation 2)
Subtract 1/3 × (equation 1) from equation 2:
{3 x + y = 4 | (equation 1)
0 x+(5 y)/3 = 20/3 | (equation 2)
Multiply equation 2 by 3/5:
{3 x + y = 4 | (equation 1)
0 x+y = 4 | (equation 2)
Subtract equation 2 from equation 1:
{3 x+0 y = 0 | (equation 1)
0 x+y = 4 | (equation 2)
Divide equation 1 by 3:
{x+0 y = 0 | (equation 1)
0 x+y = 4 | (equation 2)
Collect results:
Answer: {x = 0
, y = 4
Answer:
3
Step-by-step explanation:
Parenthesis
Exponents
Multiplication
Division
Addition
Subtraction
3^4 +9^2÷3^3-9^2
81+81÷27-81
81+3-81
3
Step-by-step explanation:
y - 3 = -1(x- -2)
y-3 = -x -2
Y = -x +1
1/2 - y (6y - 8)
1/2 -6y2 - 8y
the answer is A